ANALISIS BIBLIOMETRIK DOMAIN KETERAMPILAN BERPIKIR TINGKAT TINGGI DALAM PENDIDIKAN ABAD 21 MENGGUNAKAN VOSVIEWER - Atika Hufiah; Afandi Afandi; Eko Sri Wahyuni (JS (JURNAL SEKOLAH), 2021)
Abstract :  Bibliometric Analysis of Higher Order Thinking Skills (HOTS) Domain in 21st Century Education Using Vosviewer.This study aims to determine the development of research on the domain of higher order thinking skills in Scopus indexed journals or proceedings from 2010-2020. Data collection is done using the Publish or Perish application with the keywords critical thinking, creative thinking, and problem solving. Microsoft Excel was used to analyze the development of the number of publications, author productivity, and top articles cited by Microsoft Excel, while to analyze the relationship between research topics, research trends, and research topics that were most frequently researched, the VOSViewer application was used. The results showed that the highest publication occurred in 2020, which was 404 publications (14.92%). The 3 most productive researchers are Dwyer, C, and Fahmi, M who produced 7 journal articles. Creative thinking is the most cited topic. Network visualization is divided into 6 clusters. The latest topics based on article data in this study include models, technology, emotional intelligence, active learning, and higher education which were most widely published in 2017-2020. The most frequently researched topic is critical thinking, followed by creative thinking, strategy, practice, and case study topics..Keyword : Bibliometric, higher order thinking skill, scopus, VOSViewer Abstrak : Analisis Bibliometrik Domain Keterampilan Berpikir Tingkat Tinggi dalam Pendidikan Abad 21 Menggunakan Vosviewer.Penelitian inibertujuan untuk mengetahui perkembanganriset-risettentang domain keterampilan berpikir tingkat tinggi padajurnalatauprosidingterindeks Scopus dari tahun 2010-2020. Pengumpulan data dilakukan menggunakan aplikasi Publish or Perish dengan kata kunci critical thinking, creative thinking, dan problem solvilng. Untuk menganalisis perkembangan jumlah publikasi, produktivitas penulis, dan top artikel yang paling banyak disitasi digunakan Microsoft Excel, sedangkan untukmenganalisishubugan antar topik riset, tren riset, dan topik riset yang paling sering diteliti digunakan aplikasi VOSViewer. Hasil penelitian menunjukkan bahwa publikasi tertinggi terjadi pada tahun 2020 yaitu sebanyak 404 publikasi (14,92%). 3 peneliti paling produktif adalah Dwyer, C dan Fahmi, M yang menghasilkan 7 artikel jurnal. Creative thinking merupakan topik yang paling banyak dikutip. Network visualization terbagi menjadi 6 klaster. Topik terbaru berdasarkan data artikel pada penelitian ini diantaranya model, technology, emotional intelligence, active learning, dan higher education paling banyak dipublikasi pada tahun 2017-2020.  Topik yang paling sering diteliti adalah critical thinking, disusul dengan topik creative thinking, strategy, practice dan case study. Kata kunci : Bibliometrik, keterampilan berpikir tingkat tinggi, jurnal, scopus, VOSViewer